2005
DOI: 10.1097/01.mlg.0000167804.82950.9e
|View full text |Cite
|
Sign up to set email alerts
|

Diameter of the Cochlear Nerve in Endolymphatic Hydrops: Implications for the Etiology of Hearing Loss in Ménière's Disease

Abstract: ELH results in significant deterioration of cochlear nerve and eighth cranial nerve maximal diameters in the guinea pig model. These findings are in accord with previous studies which detected ultrastructural evidence of dendritic damage and indicate that neural injury is of sufficient severity to result in light microscopic evidence of cochlear nerve and eighth cranial nerve deterioration. These data support the concept that the principle pathological insult in ELH is a form of neurotoxicity, especially in li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 49 publications
3
33
3
Order By: Relevance
“…However, studies have shown a decreased number of radial afferent nerve endings and synapses at the base of the inner and outer hair cells with no significant change in the number of hair cells (5). Similar findings were reported in the guinea pig cochlea with induced ELH (6,7) and in experimentally induced glutamate excitotoxicity (8,9). Several lines of evidence suggest that elevated levels of glutamate result in acute swelling of radial afferent dendrites and the death of type I spiral ganglion cells (10,11) with relative preservation of the hair cells (8,12,13) similar to that observed in MD-related ELH.…”
supporting
confidence: 78%
“…However, studies have shown a decreased number of radial afferent nerve endings and synapses at the base of the inner and outer hair cells with no significant change in the number of hair cells (5). Similar findings were reported in the guinea pig cochlea with induced ELH (6,7) and in experimentally induced glutamate excitotoxicity (8,9). Several lines of evidence suggest that elevated levels of glutamate result in acute swelling of radial afferent dendrites and the death of type I spiral ganglion cells (10,11) with relative preservation of the hair cells (8,12,13) similar to that observed in MD-related ELH.…”
supporting
confidence: 78%
“…Experimental data both from human as well as animal models of the disorder have generally failed to determine the mechanism by which ELH or related pathology causes hearing loss. However, a limited number of detailed ultrastructural studies have demonstrated significant reductions in dendritic innervation densities, raising the possibility that neurotoxicity plays an important role in the pathology of MD [3]. Increasing evidence suggests that oxidative stress is involved in the development of endolymphatic hydrops and that cellular damage and apoptotic cell death might contribute to the sensorineural hearing loss found in later stages of MD [4].…”
Section: Introductionmentioning
confidence: 95%
“…The cause of Meniere's disease remains unclear, although numerous causative factors have been considered in the development of hydrops and in the pathogenesis of related cochleovestibular dysfunction [3]. Experimental data both from human as well as animal models of the disorder have generally failed to determine the mechanism by which ELH or related pathology causes hearing loss.…”
Section: Introductionmentioning
confidence: 99%
“…An intriguing set of findings, with implications for drug selection, indicates that spiral ganglion cell damage is associated with endolymphatic hydrops (43,44). It may be that the initial site leading to distension of Reissner's membrane is some type of neuronal insult (45).…”
Section: Discussionmentioning
confidence: 98%